PENGARUH LABEL BPOM, ELECTRONIC WORD OF MOUTH, DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PRODUK SKINCARE (Studi Pada Mahasiswa STIE Tamansiswa Banjarnegara) - Meiliani, Herlinge; Suryani, Ratna; Lusaputra, Fadhil Ghani (Medikonis, 2025)
ABSTRAC Competition in the business world is currently growing quite rapidly and has led to the emergence of various competitions between companies. Skincare products currently come in various variants and have an important role in maintaining skin health. This encourages public interest, especially the younger generation, in skincare products. The purpose of this study was to determine the effect of BPOM labeling, electronic word of mouth and brand trust on buying interest in skincare products, a case study of STIE Tamansiswa Banjarnegara students. This study uses quantitative methods by distributing questionnaires. Sampling using purposive sampling technique obtained a sample of 90 respondents. In this study using multiple regression analysis with the help of the SPSS version 27 program. The results of this study indicate that partially there is a significant influence between the BPOM label variable and electronic word of mouth on purchase intention. While the brand trust variable partially has no influence on buying interest. There is a simultaneous influence between the BPOM label, electronic word of mouth, and brand trust on buying interest. In addition, the R Square value is 0.457 which indicates that the independent variable affects the dependent variable by 45.7%, while the remaining 54.3% is influenced by other variables not included in this study.